Notes on Early Land Plants Today. 74. Validation of a few names in liverworts (Marchantiophyta) - Söderström, Lars; Pócs, Tamás; Váňa, Jiří; Hagborg, Anders (Phytotaxa, 2015)
For the forthcoming world checklist of hornworts and liverworts (Söderström et al. in press) a few names to be used need to be validated.